Haptic Exploratory Procedures of Children and Youth with and without Cerebral Palsy - Taylor, S.; Girdler, Sonya; McCutcheon, S.; McLean, B.; Parsons, R.; Falkmer, Torbjorn; Jacoby, P.; Carey, L.; Elliott, Catherine (Informa Healthcare, 2018)
Aims: Compare haptic exploratory procedures (EPs) and exploratory movements (EMs) of children. This study also tested the interrater reliability of a novel digital recording method. Methods: Participants were 31 children with typical development (TD) (aged 6 years 1 month to 15 years 9 months; 14 male) and 23 children with spastic unilateral cerebral palsy (CP) (aged 6 years to 15 years 5 months; 13 males; right hemiplegia, n = 12). Results: There were no statistically significant differences between groups for expected EP (p = .15), additional EPs (p = .78), or EMs (p = .69) but there was for mean duration of exploration (p < .001) and accuracy (p < .001). This suggests that although children with CP performed similar haptic EPs for each object as children with TD, they took more time and were less accurate in their identification. There was substantial agreement between the two raters' observations of expected EP, κ = .64, p < .0005. Conclusion: Children with CP performed similar haptic EPs as their TD peers. However, despite similarities, the results indicate that for children with CP manual ability was not the primary determinant of accuracy or speed of identification. This study provides evidence for a reliable method of recording haptic EPs.